Physicochemical and structural characterisation of oil palm trunks (OPT) hydrochar made via wet torrefaction - Megan, Soh; Deni Shidqi, Khaerudini; Chung Loong, Yiin; Jiuan Jing, Chew; Jaka, Sunarso (Elsevier Ltd., 2022)
This study evaluates the effect of wet torrefaction of OPT under autogenous pressures at 3 different relatively low temperatures (i.e. 180, 200, and 220 oC) and extended residence times (i.e. 3, 6, 9, 12, 18, 24, 48, and 72 h) on the hydrochar's physical, chemical, and structural properties. Logarithmic-like increase of HHV profile was observed at the highest temperature of 220 oC, in which a plateau was reached at 24 h. Between temperature and residence time, temperature gave a more significant influence on the characteristics of the produced biochar. The HHV of the biomass sample increases from 16.4 MJ kg−1 in raw OPT to the highest HHV of 26.9 MJ kg−1 when torrefied at 220 oC for 72 h. Van Krevelen analysis shows dehydration was the primary reaction pathway that occurred during wet torrefaction of OPT at 180 oC for 24 h, 200 oC for 24 h, 220 oC for 6 h, and 220 oC for 12 h. Decarboxylation dominates the reaction when temperature and residence time was increased to 220 oC for 24 h, respectively. Further increasing the residence time to 48 and 72 h at 220 oC promotes demethylation as the dominant reaction. FTIR analysis reveals that most hemicellulose and parts of cellulose decomposed when OPT was subjected to lower temperature and/or residence time (i.e. 180 oC for 24 h, 200 oC for 24 h, 220 oC for 6 h, and 220 oC for 12 h). However, increasing temperature to 220 oC and beyond 24 h resulted in carbon-rich and lignin-dense hydrochar, which was observed in powder XRD results where graphite nitrate peak at 2θ of 7.4o appears. Morphology analysis reveals that most of the hemicellulose and cellulose-rich parenchyma was removed when subjected to wet torrefaction at 220 oC for 24 h. The formation of microspheres from the repolymerisation of 5-HMF was observed in large quantities in OPT hydrochar treated at 220 oC for 72 h. Inorganic elemental analysis shows that wet torrefaction of OPT effectively removes K and Cl from the biomass. The removal of K increased with increased temperature, which may partially resolve the corrosion problems in combustion reactions related to silicate deposition. OPT hydrochar from WT under autogenous condition and relatively low temperature exhibits much more improved fuel properties compared to raw OPT.